Prospective comparison of 68Ga-FAPI-04 and 18F-FDG PET/CT for tumor staging in nasopharyngeal carcinoma - Ding, Haoyuan; Liang, Juan; Qiu, Lin; Xu, Tingting; Cai, Liang; Wan, Qiang; Wang, Li; Liu, Ya; Chen, Yue (Frontiers in Oncology, 2022)
Purpose: To explore the difference in the effectiveness of gallium-68 fibroblast activation protein inhibitor (68Ga-FAPI-04) PET/CT and fluorine-18 fluorodeoxyglucose (18F-FDG) PET/CT for the initial staging of patients with nasopharyngeal carcinoma (NPC). Methods: The Affiliated Hospital of Southwest Medical University hosted this single-center prospective investigation (Clinical Trials registration No.ChiCTR2100044131) between March 2020 and September 2021. Within a week, all subjects underwent MR scans, 68Ga-FAPI-04 PET/CT, and 18F-FDG PET/CT in order. The effectiveness of medical staging employing 68Ga-FAPI-04 and 18F-FDG PET/CT was compared. Results: Twenty-eight patients with primary NPC were evaluated (mean age53 ± 11 years). 68Ga-FAPI-04 PET/CT indicated an elevated recognition rate for diagnosing primary tumors (28/28 [100%] vs. 27/28 [96%]) and lymph node metastases (263/285 [92%] vs. 228/285 [80%]), but a lower detection rate for distant metastases (5/7 [71%] vs. 7/7 [100%]) compared with 18F-FDG PET/CT. A significant association between the maximum standard uptake value (SUVmax) of 18F-FDG PET and 68Ga-FAPI-04 PET was found in the primary cancers (r = 0.691, p < 0.001). In comparison to 18F-FDG PET/CT, 68Ga-FAPI-04 PET/CT upstaged the T stage in five patients while downstaging the N stage in seven patients. 68Ga-FAPI-04 PET/CT corrected the overall staging of five patients on18F-FDG PET/CT. Conclusion: 68Ga-FAPI-04 PET/CT is preferable to 18F-FDG PET/CT for NPC staging in terms of the detection efficiency for primary tumors and lymph node metastasis. This is especially true when evaluating the primary cancer and any spread to contiguous tissues. It is possible to improve the staging assessment of NPC by using 68Ga-FAPI-04 PET/CT in conjunction with 18F-FDG PET/CT.